Frontotemporal dementia: peculiarities of clinical variants - Klimbytė, B.; Vaitkus, A. (Neurologijos seminarai, 2021)
Frontotemporal dementia (FTD) is a group of neurodegenerative diseases that cause atrophy of the frontal and temporal lobes of the brain. The most common clinical variants of FTD are a behavioural variant characterized by disinhibition, apathy, lack of empathy, stereotyped or compulsive behaviour and hyperorality, and primary progressive aphasia which may be semantic or non- fluent. Semantic variant presents with anomia, surface dyslexia, and single-word comprehension deficits, while non-fluent variant is characterized by apraxia of speech and agrammatism in language production. The heterogeneous clinical manifestations of FTD lead to diagnostic challenges in day-to-day clinical practice. Conventional neuropsychological tests used in the diagnosis of Alzheimer’s disease are not sensitive enough to assess cognitive impairment in the frontal lobes. The most frequent clinical variants, differential diagnosis, diagnostic methods, and treatment options of FTD are discussed in this literature review.
Keywords: frontotemporal dementia; early-onset dementia